Evaluation of curriculum and student learning needs using 360 degree assessment - Ladyshewsky, Rick; Taplin, Ross (Routledge, 2014)
This research used a 360 degree assessment tool modelled from the competing values framework to assess the curriculum. A total of 100 Master’s of Business Administration students and 746 of their work colleagues completed the 360 degree assessment tool. The students were enrolled in a course on leadership and management. The results of the assessment demonstrated similar patterns of strengths and development needs between the mean self-assessment of the students and those of their work colleagues, although work colleagues tended to assess the students slightly higher. The patterns revealed development needs in soft skills such as conflict management and mentoring, as well as in strategic management and project planning. Gender effects were evident with women needing particular development in competencies related to developing and communicating a vision, setting goals and objectives and designing and organising. The results provide evidence-based approach to assessing curriculum. As many programmes use a variety of assessment tools in their programmes, collecting data across cohorts can be a valuable evidence-based strategy to assess and evaluate curriculum content against real learner needs.